2016
DOI: 10.1016/j.berh.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Models of Care for secondary osteoporotic fracture prevention and orthogeriatric Models of Care for osteoporotic hip fracture

Abstract: As the world's population ages, the prevalence of osteoporosis and its resultant fragility fractures is set to increase dramatically. This chapter focuses on current frameworks and major initiatives related to the implementation of fracture liaison services (FLS) and orthogeriatrics services (OGS), Models of Care designed to reliably implement secondary fracture prevention measures for individuals presenting to health services with fragility fractures. The current evidence base regarding the impact and effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 64 publications
0
39
0
Order By: Relevance
“…Not only did FLS yield higher rates of diagnosis and treatment in comparison with other programs, it also improved accessibility to the post-fracture pathway of care, supporting a patientcentered healthcare approach [4]. With regard to the most common fracture sites, the benefits of FLS programs were more significant in non-vertebral (i.e., femur and humerus) than in vertebral fractures [25], probably because there were more therapeutic and diagnostic procedures requested by the latter [26,27]. With regard to the economic benefits, the financial value of FLS relies on the prevention of a high human and monetary burden.…”
Section: Type D (0-i)mentioning
confidence: 98%
See 1 more Smart Citation
“…Not only did FLS yield higher rates of diagnosis and treatment in comparison with other programs, it also improved accessibility to the post-fracture pathway of care, supporting a patientcentered healthcare approach [4]. With regard to the most common fracture sites, the benefits of FLS programs were more significant in non-vertebral (i.e., femur and humerus) than in vertebral fractures [25], probably because there were more therapeutic and diagnostic procedures requested by the latter [26,27]. With regard to the economic benefits, the financial value of FLS relies on the prevention of a high human and monetary burden.…”
Section: Type D (0-i)mentioning
confidence: 98%
“…Another study based in the UK found that FLS implementation over a 5-year period saved £290,708 in National Health Service (NHS) acute services, community services, and local authority social costs, as opposed to an additional £234,181 in revenue, covering drug treatment for the same period [29]. From a public health perspective, FLS is, therefore, expected to generate long-term health and economic benefits, both, for the patients and the community, thereby supporting healthcare continuity and culture [26], which is a key-determinant of healthcare value [30][31][32][33]. Table 4.…”
Section: Benefits Of Fls As Reported In Literaturementioning
confidence: 99%
“…The slight increase in the number of patients prescribed with vitamin D supplements in the first months after hip fracture might refers to the group of subjects appropriately referred to fracture liaison services activated within the hospitals where the orthopedic treatment for hip fracture was first performed. Indeed, group of patients can be appropriately referred to these services for the commencement of programs of secondary prevention of re-fracture (14). These procedures have to be encouraged and reinforced in order to address these patients towards effective programs of secondary prevention against refracture.…”
Section: Discussionmentioning
confidence: 99%
“…These patients are often too frail to attend outpatient appointments and OGS is valuable for the secondary prevention of fractures in these cases. 30 High-quality and standardized care requires the development of specific local protocols based on national guidelines, to ensure clear directives on the delivery of post fragility fracture care. There is an ongoing debate among service leaders about the best way to organize and deliver a FLS.…”
Section: A Gap In Carementioning
confidence: 99%